FENCING OF HOUSEHOLD PLOTS: FUNCTIONS, MATERIALS, AND DESIGN - Berezovetska І.; Dudiak Н. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The article presents a comprehensive analysis of fencing as a key element in the architectural-planning and functional organization of a household plot. Fences are considered not only as a means of physical protection and territorial boundary delineation, but also as a structural component of the landscape environment, shaping the overall perception of space, ensuring privacy, and playing an important role in the visual identity of the site. A typology of fences is provided based on materials (wood, metal, concrete, stone, combined structures, mesh, green hedges), structural characteristics, and functional purpose. Particular attention is paid to the compliance of fencing with regulatory and legal requirements, construction standards, and neighborly relations, especially regarding height, transparency, sanitary, and insolation restrictions. Contemporary trends in the arrangement of household fences are analyzed, including the use of environmentally friendly materials, vertical landscaping, and integration with small architectural forms and other landscaping elements. The article describes the structural components of fences (foundations, posts, panel infill, gates, wickets), their placement, and engineering-aesthetic solutions that ensure durability and decorative appeal. Based on the study, practical recommendations are formulated for selecting fence types considering functional needs, budget, architectural style of the house, climatic conditions, and specific features of land use. It is emphasized that competent fence design is essential for creating a comfortable, safe, and visually attractive living space.